2022
DOI: 10.3389/fsurg.2022.853643
|View full text |Cite
|
Sign up to set email alerts
|

Non-intubated Thoracic Surgery: Wedge Resections for Peripheral Pulmonary Nodules

Abstract: The feasibility of performing pulmonary resections of peripheral lung nodules has been one of the main objectives of non-intubated thoracic surgery. The aim was to obtain histological characterization and extend a radical intended treatment to oncological patients unfit for general anesthesia or anatomic pulmonary resections. There is mounting evidence for the role of wedge resection in early-stage lung cancer treatment, especially for frail patients unfit for general anesthesia and anatomic resections with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…More often, nonintubated techniques have been used in minor thoracic surgeries involving low-risk patients; however, advancements in technology and increased experience have demonstrated that these techniques are safe and applicable in more complicated procedures for selected and high-risk patients. Their good safety profile has been shown in surgeries such as pulmonary nodule resections, [4,10,37,38] pleural and pericardial effusions, [39] pneumothorax, [40][41][42] biopsies, [43][44][45] thymectomy, [46][47][48] volume reduction surgeries, [29,49] segmentectomy, [50,51] and lobectomy. [26,52,53] In the past, patients with American Society of Anesthesiologists grades 1-2, body mass index of <30, cardiopulmonary stability, and no expectation for difficult airway were preferred for nonintubated techniques.…”
Section: Patient Selectionmentioning
confidence: 99%
“…More often, nonintubated techniques have been used in minor thoracic surgeries involving low-risk patients; however, advancements in technology and increased experience have demonstrated that these techniques are safe and applicable in more complicated procedures for selected and high-risk patients. Their good safety profile has been shown in surgeries such as pulmonary nodule resections, [4,10,37,38] pleural and pericardial effusions, [39] pneumothorax, [40][41][42] biopsies, [43][44][45] thymectomy, [46][47][48] volume reduction surgeries, [29,49] segmentectomy, [50,51] and lobectomy. [26,52,53] In the past, patients with American Society of Anesthesiologists grades 1-2, body mass index of <30, cardiopulmonary stability, and no expectation for difficult airway were preferred for nonintubated techniques.…”
Section: Patient Selectionmentioning
confidence: 99%